Using Compression-Only CPR Mini-Training Sessions to Address Rural Bystander Care - Cassity Gutierrez; Eric Rupe; Cody Arlie Reed; Becky Wolff (Rural Nurse Organization; Binghamton University, 2020)
Purpose: Rural populations face vast disparities in out-of-hospital cardiac arrest survival rates when compared with urban populations. Furthermore, rural areas have lower CPR training rates. Compression-Only CPR (COCPR) is a simplified resuscitation method that eliminates the task of rescue breathing. The simplified nature can significantly reduce training times and be more comprehendible and convenient for the general population. The purpose of this study is to assess the change in knowledge and self-confidence of rural college students to administer COCPR as a result of mini-training sessions. Sample: Purposive sampling was used to focus on the 125 rural college students who received a COCPR mini-training session at the medium sized University located in a rural state with a historically low CPR training rate. Method: Each participant completed a 14 question pre-survey, the COCPR training, and 13 question post-survey. Descriptive statistics on the pre-, post-, and subscale change scores for both knowledge and self-confidence were computed and one-way between subjects ANOVAs were conducted to determine differences between group means related to prior CPR training. Findings: The training resulted in a positive increase in the participants' knowledge and confidence to administer care. Furthermore, the participants indicated that they would recommend this training to others. Conclusions: This study provides insight into the viability of providing COCPR in lieu of conventional CPR, supports having individuals trained at an earlier age to provide bystander care, and supports training individuals in rural areas where response time is delayed. DOI: http://dx.doi.org/10.14574/ojrnhc.v20i1.593 Keywords: Rural, Bystanders, CPR, Compression Only, Cardiopulmonary Resuscitation, Cardiac Arrests